(untitled) - Filova, Eva; David, Andrej; Sosedova, Jarmila (Doprava a spoje, 2012)
Tourist industry in the content of the development of water tourism in the conditions of the Slovak Republic. The rating of selected tourism centres - micro region Medzibodrozie, Liptov, Orava, micro region Zemplinska Sirava, Dolne Povazie - related the rivers / water areas (the rivers such as the Bodrog and the Vah, water areas like Liptovska Mara, Orava dam, Zemplinska Sirava) through multi objective analysis or proportionality - index method.